Connecting Scientists Residing Abroad: A Review of Converciencia as a Practice to Engage the Guatemalan Scientific Diaspora From 2005–2020 - Bonilla, Kleinsy; Arrechea, Susana; Velásquez Pérez, Luis Guillermo (Frontiers in Research Metrics and Analytics, 2022)
In 2005, the Guatemala National Secretariat of Science and Technology (Senacyt) introduced Converciencia, a program designed to connect Guatemalan scientists residing abroad with their country of origin. Converciencia has been a flagship practice for over 15 years. This program involves three main groups of participants: (i) science and technology (S&T) policy agents, (ii) the scientific community (including parts of the Guatemala scientific diaspora - GSD), and (iii) host institutions (local co-organizers, mainly universities and research institutes). This article presents a comprehensive and balanced overview of the Converciencia program applying an in-depth analysis of its creation, evolution, leading trends, and legacies. Using qualitative methodology, applying a four-level analysis (descriptive, explanatory, normative, and prescriptive) allowed the identification of nuances of this S&T practice in the context of a scientifically lagging country such as Guatemala. Detailed data collected through documentary and desk review, gray literature, focus group discussions, and semi-structured interviews resulted in a framework to highlight the strengths, weaknesses, opportunities, and threats (SWOT) in the planning, organization, implementation, monitoring, and perception of the results achieved by Converciencia. Findings portray the contrasting views and perceptions from a single S&T practice, depending on the participating parties’ roles and responsibilities. Direct participants examined how Converciencia has achieved its objectives while questioning the effectiveness and impact that the resources allocated (financial, human) to the initiative have yielded over time. Evidence indicates that, despite the design, coordination, and evaluation limits of Converciencia, the GSD, the scientific community in Guatemala, and the host institutions are interested in the continuity of the practice. Indeed, the main recommendation involves restructuring and turning Converciencia into a robust S&T policy. Converciencia as a policy engaging the GSD could produce greater results and impacts by involving all the key actors in co-designing activities, clearly determining roles and responsibilities, and establishing performance and impact indicators for evaluation.